Aspects of Zola's L'Assommoir - Thomas, Ralph J. (My University, 1974)
Genesis and background of L'Assommoir and a study of various techniques employed by Zola in the novel. Particular emphasis on his evocation of the physical environment (including people) and its relationship to, and effects upon, the character of Gervaise.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures